"Dubai is a transit lounge": Migration, temporariness and belonging among Pakistani middle-class migrants. (June 2021) - Errichiello, Gennaro; Nyhagen, Line
This article discusses relationships between temporariness and belonging among Pakistani middle-class migrants in Dubai. We explore reasons that push them to move to Dubai and how their professional position and temporary status affect their sense of belonging. Based upon unstructured interviews with 20 Pakistanis, our findings show that temporariness is problematized, but not explicitly contested, by the participants, who all expressed a strong sense of belonging to Dubai despite their lack of citizenship rights. We suggest that these findings relate to the participants' ability to draw upon socio-economic resources and networks to enable further transnational mobility.